Water and social policy - Pawar, Manohar; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Manohar Pawar discusses the relevance and importance of social policy for water issues. By analysing several interrelated perspectives on water, he suggests core values as bases for formulating and implementing social policies so as to provide universal free access to safe drinking water for all, particularly for the most poor and disadvantaged.
Keywords: Science; Science, general